Liquid crystal polymer composition

JP7643720B2Active Publication Date: 2025-03-11UENO PHARMA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021091705
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-31
Publication Date
2025-03-11
Estimated Expiration
2041-05-31

AI Technical Summary

Benefits of technology

【0013】 本発明の液晶ポリマー組成物は、通常の成形材料として使用されるほか、その柔軟性に基づき製膜性が改善されるため、フィルム、シート、ブロー成形品として好適に使用される。 本明細書において製膜性とは、フィルム、シート、ブロー成形品等を形成する工程において成形温度または含有成分の熱劣化に起因する諸問題を生ないこと、しかも、その柔軟性に基づきフィルム、シート、ブロー成形品等が比較的低い成形温度で得られることを含む特性を指称する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643720000001
    Figure 0007643720000001
  • Figure 0007643720000002
    Figure 0007643720000002
  • Figure 0007643720000003
    Figure 0007643720000003
Patent Text Reader

Abstract

To provide a liquid crystal polymer composition having improved film forming properties.SOLUTION: A liquid crystal polymer composition contains a wholly aromatic liquid crystal polymer with a crystal melting temperature of 210-250°C of 100 pts.mass and a polyamide resin of 1-100 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal polymer composition containing a specific liquid crystal polymer and a polyamide resin, and having improved film-forming properties. [Background technology]

[0002] Thermotropic liquid crystal polymers (hereinafter referred to as liquid crystal polymers or LCPs) are excellent in mechanical properties such as heat resistance and rigidity, chemical resistance, dimensional accuracy, dielectric properties, etc., and therefore their use is expanding not only in molded products but also in various applications such as fibers and films. Furthermore, because of their excellent gas barrier properties, they are expected to be used as packaging materials.

[0003] However, when liquid crystal polymers are processed into films, there is a problem that the liquid crystal polymers are difficult to mold into films because they have a rigid molecular structure and tend to be oriented in the molding direction, exhibiting anisotropy, or tend to tear in the molding direction.

[0004] Therefore, various methods have been proposed to improve the film formability of liquid crystal polymers. For example, Patent Document 1 proposes a film made of a blend resin of a liquid crystal polymer and an ethylene copolymer having a glycidyl group, and Patent Documents 2 and 3 propose a film formed from a blend resin of a liquid crystal polymer and a thermoplastic resin such as polyarylate.

[0005] Furthermore, Patent Document 4 proposes a resin composition that is excellent in heat resistance and flexural modulus at high temperatures and that is less susceptible to dimensional change due to water and moisture absorption, by blending a specific liquid crystal polyester with polyamide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 08-337710 [Patent Document 2] JP 2000-290512 A [Patent Document 3] JP 2004-175995 A [Patent Document 4] Japanese Patent Application Publication No. 09-031310 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the film made of the blended resin described in Patent Document 1 uses a liquid crystal polymer having a flow initiation temperature of 260° C. or higher, and there is a possibility that the ethylene copolymer may be thermally deteriorated during film formation.

[0008] In addition, the films made of the blended resins described in Patent Documents 2 and 3 use liquid crystal polymers with a melting point of 250°C or higher, and therefore lamination with general-purpose resins is difficult in terms of processing temperature, so that their applications are limited and their film-forming properties are insufficient.

[0009] Furthermore, Patent Document 4 describes a resin composition in which a liquid crystal polyester is blended with a polyamide in order to reduce the water absorption and moisture absorption of the polyamide, but does not consider improving the film-forming properties of a wholly aromatic liquid crystal polymer.

[0010] An object of the present invention is to provide a liquid crystal polymer composition having improved film-forming properties. [Means for solving the problem]

[0011] In view of the above problems, the present inventors conducted intensive research and discovered that by blending a specific liquid crystal polymer with a predetermined amount of polyamide resin, a liquid crystal polymer composition with improved film-forming properties can be obtained, thereby completing the present invention.

[0012] That is, the present invention includes the following preferred embodiments. [1] A liquid crystal polymer composition comprising 100 parts by mass of a wholly aromatic liquid crystal polymer having a crystalline melting temperature of 210 to 250° C. or less and 1 to 100 parts by mass of a polyamide resin. [2] The liquid crystal polymer composition according to [1], wherein the wholly aromatic liquid crystal polymer has a crystalline melting temperature of 215 to 245°C. [3] The wholly aromatic liquid crystal polymer is represented by the formulas (I) to (IV) [ka] [In the formula, Ar1 and Ar2 each represent one or more divalent aromatic groups, and p, q, r and s each represent the composition ratio (mol %) of each repeating unit in the wholly aromatic liquid crystal polyester, and satisfy the following condition: 0.5≦p / q≦2.5 2 ≤ r ≤ 15, and 2≦s≦15] The liquid crystal polymer composition according to [1] or [2], which is a wholly aromatic liquid crystal polyester containing a repeating unit represented by the following formula: [4] In the formula (III) and / or formula (IV), Ar1 and Ar2 are each independently represented by any one of the formulas (1) to (4). [ka] The liquid crystal polymer composition according to [3], comprising one or more repeating units which are aromatic groups selected from the group consisting of: [5] The liquid crystal polymer composition according to any one of [1] to [4], wherein the polyamide resin is polyamide 6. [6] A molded article made of the liquid crystal polymer composition according to any one of [1] to [5]. [7] The molded article according to [6], which is a film, a sheet or a blow molded article. Effect of the Invention

[0013] The liquid crystal polymer composition of the present invention can be used as a normal molding material, and also can be suitably used as a film, sheet or blow molded product because of its improved film formability due to its flexibility. In this specification, film formability refers to the property of not causing problems due to the molding temperature or thermal degradation of the components in the process of forming a film, sheet, blow molded article, etc., and further, the property of being able to obtain a film, sheet, blow molded article, etc. at a relatively low molding temperature due to its flexibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The wholly aromatic liquid crystal polymer used in the liquid crystal polymer composition of the present invention is a wholly aromatic liquid crystal polyester or a wholly aromatic liquid crystal polyester amide which forms an anisotropic molten phase and is called a thermotropic liquid crystal polymer by those skilled in the art.

[0015] The anisotropic melt phase properties of the wholly aromatic liquid crystal polymer can be confirmed by a conventional polarimetric inspection method using cross polarizers, that is, by observing a sample placed on a hot stage under a nitrogen atmosphere.

[0016] Examples of the repeating units constituting the wholly aromatic liquid crystal polymer used in the present invention include aromatic oxycarbonyl repeating units, aromatic dicarbonyl repeating units, aromatic dioxy repeating units, aromatic aminooxy repeating units, aromatic diamino repeating units, aromatic aminocarbonyl repeating units, and combinations thereof.

[0017] Specific examples of monomers that provide aromatic oxycarbonyl repeating units include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 2-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as their alkyl, alkoxy, or halogen-substituted derivatives, and their acylated derivatives, ester derivatives, acid halides, and other ester-forming derivatives. Among these, 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid are preferred because they are easy to adjust the mechanical properties, heat resistance, crystal melting temperature, and moldability of the resulting wholly aromatic liquid crystal polymer to appropriate levels.

[0018] Specific examples of monomers that provide aromatic dicarbonyl repeating units include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, and 4,4'-dicarboxybiphenyl, as well as their alkyl, alkoxy, or halogen-substituted derivatives, and their ester-forming derivatives such as ester derivatives and acid halides. Among these, terephthalic acid and 2,6-naphthalenedicarboxylic acid are preferred because they are easy to adjust the mechanical properties, heat resistance, crystal melting temperature, and moldability of the resulting wholly aromatic liquid crystal polymer to appropriate levels.

[0019] Specific examples of the monomer that gives the aromatic dioxy repeating unit include aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, and their alkyl, alkoxy or halogen-substituted derivatives, as well as their acylated derivatives and other ester-forming derivatives. Among these, hydroquinone and 4,4'-dihydroxybiphenyl are preferred because they are easy to adjust the reactivity during polymerization, the mechanical properties, heat resistance, crystal melting temperature and moldability of the resulting wholly aromatic liquid crystal polymer to an appropriate level.

[0020] Monomers which provide the aromatic aminooxy repeating unit, aromatic diamino repeating unit and aromatic aminocarbonyl repeating unit include aromatic hydroxyamines, aromatic diamines and aromatic aminocarboxylic acids.

[0021] The wholly aromatic liquid crystal polymer used in the present invention may contain an aromatic oxydicarbonyl repeating unit or a thioester bond, provided that the object of the present invention is not impaired. Examples of monomers that give thioester bonds include mercaptoaromatic carboxylic acids, aromatic dithiols, and hydroxyaromatic thiols. The amount of these monomers used is preferably 10 mol% or less based on the total amount of the aromatic oxycarbonyl repeating unit, aromatic dicarbonyl repeating unit, aromatic dioxy repeating unit, aromatic aminooxy repeating unit, aromatic diamino repeating unit, and monomers that give aromatic aminocarbonyl repeating units.

[0022] Among copolymers combining these repeating units, some form an anisotropic molten phase and some do not, depending on the monomer composition and composition ratio, and the sequence distribution of each repeating unit in the copolymer. However, the wholly aromatic liquid crystal polymer used in the present invention is limited to copolymers that form an anisotropic molten phase.

[0023] The wholly aromatic liquid crystal polymer used in the present invention may be a blend of two or more liquid crystal polymers.

[0024] The crystalline melting temperature of the wholly aromatic liquid crystal polymer used in the present invention, as measured by a differential scanning calorimeter, is 210 to 250°C, preferably 212 to 248°C, and more preferably 215 to 245°C.

[0025] Since the crystalline melting temperature of the wholly aromatic liquid crystal polymer is 210 to 250°C, the polyamide resin is easily dispersed in the composition without thermal degradation during molding processing, improving moldability into films, sheets, blow molded products, etc., and also enabling blending or lamination with general-purpose resins such as polyethylene, polypropylene, and polyethylene terephthalate.

[0026] In the present specification and claims, the "crystalline melting temperature" is determined from the crystalline melting peak temperature measured at a heating rate of 20°C / min using a differential scanning calorimeter (hereinafter abbreviated as DSC). More specifically, after observing the endothermic peak temperature (Tm1) observed when a sample of a wholly aromatic liquid crystal polymer is measured under a heating condition of 20°C / min from room temperature, the sample is held at a temperature 20 to 50°C higher than Tm1 for 10 minutes, and then cooled to room temperature under a heating condition of 20°C / min, and then measured again under a heating condition of 20°C / min. The temperature showing the peak top is taken as the crystalline melting temperature of the wholly aromatic liquid crystal polymer. For example, Exstar6000 manufactured by Seiko Instruments Inc. can be used as a measuring instrument.

[0027] As the wholly aromatic liquid crystal polymer used in the present invention, wholly aromatic liquid crystal polyesters are preferably used, and wholly aromatic liquid crystal polyesters containing repeating units represented by formulae (I) to (IV) are more preferably used. [ka]

[0028] [In the formula, Ar1 and Ar2 each represent one or more divalent aromatic groups, and p, q, r and s each represent the composition ratio (mol %) of each repeating unit in the wholly aromatic liquid crystal polyester, and satisfy the following condition: 0.5≦p / q≦2.5 2 ≤ r ≤ 15, and 2≦s≦15.]

[0029] The molar ratio (p / q) of the composition ratio p (mol %) according to the above formula (I) to the composition ratio q (mol %) according to the above formula (II) is more preferably from 0.6 to 1.8, and further preferably from 0.8 to 1.6.

[0030] In the above-mentioned wholly aromatic liquid crystal polyesters which are suitably used, the total composition ratio of p and q is preferably from 70 to 96 mol %, and more preferably from 76 to 90 mol %.

[0031] In the above-mentioned wholly aromatic liquid crystal polyesters which are preferably used, the composition ratio p in formula (I) and the composition ratio q in formula (II) are each preferably 32 to 54 mol %, more preferably 36 to 52 mol %.

[0032] In the wholly aromatic liquid crystal polyester preferably used in the present invention, by containing the repeating units represented by formula (I) and formula (II) at least in the above-mentioned molar ratio (p / q), and optionally in the above-mentioned total composition ratio of p and q and / or each of p and q in the above-mentioned composition ratio (mol %), a wholly aromatic liquid crystal polyester exhibiting a crystalline melting temperature of 250°C or less can be preferably obtained.

[0033] In the wholly aromatic liquid crystal polyester preferably used in the present invention, the composition ratio r of formula (III) and the composition ratio s of formula (IV) are each preferably 2 to 15 mol %, more preferably 5 to 12 mol %. r and s are preferably equimolar amounts.

[0034] In the above repeating units, for example, Ar1 (or Ar2) represents two or more kinds of divalent aromatic groups means that the wholly aromatic liquid crystal polyester contains two or more kinds of repeating units represented by formula (III) (or (IV)) according to the type of divalent aromatic group. In this case, the composition ratio r of formula (III) (or the composition ratio s of formula (IV)) represents the total composition ratio of two or more kinds of repeating units.

[0035] Specific examples of monomers which provide the repeating unit represented by formula (I) include 4-hydroxybenzoic acid and its ester-forming derivatives such as acylation products, ester derivatives and acid halides.

[0036] Specific examples of monomers which provide the repeating unit represented by formula (II) include 6-hydroxy-2-naphthoic acid and its ester-forming derivatives such as acylation products, ester derivatives and acid halides.

[0037] Specific examples of monomers that provide the repeating unit represented by formula (III) include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, and the like, as well as alkyl, alkoxy, or halogen-substituted derivatives thereof, and ester-forming derivatives thereof such as ester derivatives and acid halides.

[0038] Specific examples of monomers that provide the repeating unit represented by formula (IV) include aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, and ester-forming derivatives thereof, such as alkyl, alkoxy or halogen substituted products, and acylated products thereof.

[0039] Furthermore, among the wholly aromatic liquid crystal polyesters preferably used in the present invention, wholly aromatic liquid crystal polyesters in which Ar1 and Ar2 relating to the repeating units represented by formulas (III) and (IV) each independently contain one or more types selected from the group consisting of aromatic groups represented by formulas (1) to (4) are more preferably used. [ka]

[0040] Among these, as the repeating unit represented by formula (III), it is particularly preferred to use aromatic groups represented by formulas (1) and (4), i.e., terephthalic acid and 2,6-naphthalenedicarboxylic acid and their ester-forming derivatives as monomers that give these repeating units, because it is easy to adjust the mechanical properties, heat resistance, crystalline melting temperature and molding processability of the resulting wholly aromatic liquid crystal polyester to appropriate levels.

[0041] As the repeating unit represented by formula (IV), it is particularly preferred to use aromatic groups represented by formulas (1) and (3), i.e., hydroquinone, 4,4'-dihydroxybiphenyl, and their ester-forming derivatives as monomers that give these repeating units, because this makes it easy to adjust the reactivity during polymerization and the mechanical properties, heat resistance, crystalline melting temperature, and molding processability of the resulting wholly aromatic liquid crystal polyester to appropriate levels.

[0042] In the above repeating unit, for example, Ar1 (or Ar2) containing two or more aromatic groups means that the wholly aromatic liquid crystal polyester contains two or more types of repeating units represented by formula (III) (or (IV)) according to the type of divalent aromatic group. That is, the wholly aromatic liquid crystal polyester of formula (III) and / or formula (IV) is preferably a wholly aromatic liquid crystal polyester containing one or more types of repeating units in which Ar1 and Ar2 are each independently an aromatic group selected from the group consisting of formulas (1) to (4). In this case, the composition ratio r according to formula (III) (or the composition ratio s according to formula (IV)) represents the composition ratio of the two or more types of repeating units in total.

[0043] In the wholly aromatic liquid crystal polyester preferably used in the present invention, the total composition ratio of the repeating units [p+q+r+s] is preferably 100 mol %, but other repeating units may be further contained within a range that does not impair the object of the present invention.

[0044] Examples of monomers which provide other repeating units constituting the wholly aromatic liquid crystal polyester preferably used in the present invention include other aromatic hydroxycarboxylic acids, aromatic hydroxyamines, aromatic diamines, aromatic aminocarboxylic acids, aromatic hydroxydicarboxylic acids, aromatic mercaptocarboxylic acids, aromatic dithiols, aromatic mercaptophenols, and combinations thereof.

[0045] Specific examples of other aromatic hydroxycarboxylic acids include 3-hydroxybenzoic acid, 2-hydroxybenzoic acid, 5-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and alkyl, alkoxy or halogen substituted derivatives thereof, as well as ester-forming derivatives thereof such as acylation products, ester derivatives and acid halides.

[0046] The total composition ratio of the repeating units provided by these other monomer components is preferably 10 mol % or less based on the total repeating units.

[0047] The method for producing the wholly aromatic liquid crystal polymer used in the present invention will now be described.

[0048] The method for producing the wholly aromatic liquid crystal polymer used in the present invention is not particularly limited, and any known polycondensation method for forming an ester bond or an amide bond from a combination of the above-mentioned monomers, such as a molten acidolysis method or a slurry polymerization method, can be used.

[0049] The melt acidolysis method is a preferred method for preparing the wholly aromatic liquid crystal polymer used in the present invention, in which the monomers are first heated to form a melt of reactants, and then the reaction is continued to obtain a molten polymer. A vacuum may be applied to facilitate removal of volatile by-products (e.g., acetic acid, water, etc.) produced in the final stage of condensation.

[0050] A slurry polymerization process is a process in which the reaction is carried out in the presence of a heat exchange fluid, and a solid product is obtained in suspension in the heat exchange medium.

[0051] In both the melt acidolysis method and the slurry polymerization method, the polymerizable monomer components used in producing the wholly aromatic liquid crystal polymer can be subjected to the reaction at room temperature in a modified form in which the hydroxyl group and / or amino group is acylated, that is, as a lower acylated product. The lower acyl group preferably has 2 to 5 carbon atoms, more preferably has 2 or 3 carbon atoms. Particularly preferred is a method in which an acetylated product of the monomer is used in the reaction.

[0052] The acylated monomer may be one that has been previously synthesized by separate acylation, or may be produced in the reaction system by adding an acylating agent such as acetic anhydride to the monomer during the production of the wholly aromatic liquid crystal polymer.

[0053] In either the molten acidolysis method or the slurry polymerization method, a catalyst may be used during the reaction, if necessary.

[0054] Specific examples of catalysts include organotin compounds (dialkyltin oxides such as dibutyltin oxide, diaryltin oxides, etc.), titanium dioxide, antimony trioxide, organotitanium compounds (alkoxytitanium silicates, titanium alkoxides, etc.), alkali and alkaline earth metal salts of carboxylic acids (potassium acetate, sodium acetate, etc.), Lewis acids (BF3, etc.), gaseous acid catalysts such as hydrogen halides (HCl, etc.), and the like.

[0055] The catalyst is used in an amount of usually 1 to 1000 ppm, preferably 2 to 100 ppm, based on the total amount of monomers.

[0056] The wholly aromatic liquid crystal polymer thus obtained through the polycondensation reaction is withdrawn in a molten state from the polymerization reaction vessel and then processed into pellets, flakes, or powder.

[0057] The liquid crystal polymer composition of the present invention contains a polyamide resin in addition to the wholly aromatic liquid crystal polymer described above, and thus the formability of the wholly aromatic liquid crystal polymer into a film or the like is improved. The polyamide resin used in the present invention is a polymer having an amide bond in the molecule, and examples thereof include polymers obtained by polymerizing α-pyrrolidone, α-piperidone, ε-caprolactam, 6-aminocaproic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, ω-laurolactam, and the like; and polymers obtained by condensation polymerization of diamines such as hexamethylenediamine, nonamethylenediamine, undecamethylenediamine, dodecamethylenediamine, metaxylylenediamine, and 1,4-bis(aminomethyl)cyclohexane, and dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, cyclohexanedicarboxylic acid, terephthalic acid, and isophthalic acid.

[0058] Specific examples of the polyamide resin used in the present invention include polyamide 6 obtained by polymerizing ε-caprolactam, polyamide 66 obtained by condensation polymerization of hexamethylenediamine and adipic acid, polyamide 610 obtained by condensation polymerization of hexamethylenediamine and sebacic acid, polyamide 6T obtained by condensation polymerization of hexamethylenediamine and terephthalic acid, polyamide 6I obtained by condensation polymerization of hexamethylenediamine and isophthalic acid, polyamide 46 obtained by condensation polymerization of diaminobutane and adipic acid, polyamide MXD6 obtained by condensation polymerization of metaxylylenediamine and adipic acid, polyamide 9T obtained by condensation polymerization of nonanediamine and terephthalic acid, polyamide 11 obtained by polymerizing 11-aminoundecanoic acid, and polyamide 12 obtained by polymerizing 12-aminododecanoic acid or ω-laurolactam. Among these, the polyamide resins used in the present invention are preferably polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 6T, polyamide 6I and polyamide 9T, and in particular, polyamide 6 is preferred because it is less susceptible to changes in physical properties and dimensions due to moisture absorption. These polyamide resins can be used alone or in combination of two or more kinds.

[0059] The polyamide 6 used in the present invention is preferably polyamide 6 having a specific gravity of 1.10 or less, and examples of commercially available products include EX-1222, EX-1030, EX-6240, etc. manufactured by Unitika Ltd.

[0060] In the liquid crystal polymer composition of the present invention, the proportion of the polyamide resin is 1 to 100 parts by mass relative to 100 parts by mass of the wholly aromatic liquid crystal polymer, and from the viewpoint of not impairing the properties of the liquid crystal polymer, the proportion is preferably 2 to 65 parts by mass, more preferably 3 to 60 parts by mass, even more preferably 4 to 50 parts by mass, and particularly preferably 5 to 15 parts by mass.

[0061] If the content of the polyamide resin is less than 1 part by mass, the effect of improving the film formability of the liquid crystal polymer composition is not sufficiently obtained, and if it exceeds 100 parts by mass, the properties such as the gas barrier property of the liquid crystal polymer tend to deteriorate.

[0062] The liquid crystal polymer composition of the present invention is characterized in that the crystalline melting temperature of the liquid crystal polymer used is 210 to 250° C., so that the polyamide resin is uniformly dispersed in the liquid crystal polymer matrix resin, and blending by melt kneading at a low temperature is possible. Therefore, the thermal decomposition of the polyamide resin is suppressed, and the resin composition can have improved film formability due to the flexibility of the composition.

[0063] Therefore, a compatibilizer is not particularly necessary when blending, but a compatibilizer may be added for the purpose of further improving the compatibility between the liquid crystal polymer and the polyamide resin. When a compatibilizer is added, the amount of the compatibilizer added is preferably 0.5 to 10 parts by mass, more preferably 1 to 5 parts by mass, based on 100 parts by mass of the liquid crystal polymer.

[0064] The liquid crystalline polymer composition of the present invention may contain, as an optional component, inorganic and / or organic fillers.

[0065] Specific examples of inorganic and / or organic fillers that may be contained in the liquid crystal polymer composition of the present invention include glass fibers, silica alumina fibers, alumina fibers, carbon fibers, potassium titanate fibers, aluminum borate fibers, aramid fibers, polyarylate fibers, polybenzimidazole fibers, talc, mica, graphite, wollastonite, dolomite, clay, glass flakes, glass beads, glass balloons, calcium carbonate, barium sulfate, titanium oxide, etc. These may be used alone or in combination of two or more.

[0066] Among these, talc is preferred because it has an excellent balance between physical properties and cost.

[0067] The inorganic and / or organic filler may be surface-treated. Examples of the surface treatment method include a method in which a surface treatment agent is adsorbed on the surface of the filler, and a method in which a surface treatment agent is added during kneading.

[0068] Examples of the surface treatment agent include reactive coupling agents such as silane coupling agents, titanate coupling agents, and borane coupling agents, and lubricants such as higher fatty acids, higher fatty acid esters, higher fatty acid metal salts, and fluorocarbon surfactants.

[0069] When an inorganic and / or organic filler is blended, the content thereof is preferably 1 to 150 parts by mass, and more preferably 10 to 100 parts by mass, per 100 parts by mass of the total amount of the wholly aromatic liquid crystal polymer and the polyamide resin.

[0070] If the content of the inorganic and / or organic filler is less than 1 part by mass, it is difficult to obtain the effect of improving the mechanical strength and heat resistance of the liquid crystal polymer composition due to the inorganic and / or organic filler, and if it exceeds 150 parts by mass, the fluidity tends to decrease. In the present invention, it is preferable that the liquid crystal polymer composition does not contain an inorganic and / or organic filler.

[0071] In addition to the wholly aromatic liquid crystal polymer and polyamide resin, other additives and resin components may be added to the liquid crystal polymer composition of the present invention, provided that the object of the present invention is not impaired.

[0072] Specific examples of other additives include, for example, lubricants such as higher fatty acids, higher fatty acid esters, higher fatty acid amides, and higher fatty acid metal salts (here, higher fatty acids refer to those having 10 to 25 carbon atoms), release agents such as polysiloxanes and fluororesins, colorants such as dyes, pigments, and carbon black, flame retardants, antistatic agents, surfactants, nucleating agents such as talc, organic phosphates, and sorbitols, antiblocking agents, antioxidants such as phosphorus-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants, weather resistance agents, heat stabilizers, and neutralizing agents. These additives can be used alone or in combination of two or more.

[0073] The total amount of other additives in the liquid crystal polymer composition is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the total amount of the wholly aromatic liquid crystal polymer and the polyamide resin.

[0074] If the total amount of other additives is less than 0.01 parts by mass, it is difficult for the additives to realize their functions, whereas if it exceeds 5 parts by mass, the thermal stability of the liquid crystal polymer composition during molding tends to deteriorate.

[0075] Furthermore, when additives such as lubricants, release agents, and antiblocking agents are used among the other additives, they may be added when preparing the liquid crystal polymer composition, or may be attached to the pellet surface of the liquid crystal polymer composition during molding.

[0076] Specific examples of other resin components include thermoplastic resins such as polyester, polyacetal, polyphenylene ether and modified products thereof, polysulfone, polyethersulfone, polyetherimide, polyamideimide, etc., and thermosetting resins such as phenol resin, epoxy resin, polyimide resin, etc. These resin components may be used alone or in combination of two or more kinds.

[0077] When other resin components are contained, the content thereof is preferably 100 parts by mass or less, and more preferably 80 parts by mass or less, per 100 parts by mass of the total amount of the wholly aromatic liquid crystal polymer and the polyamide resin.

[0078] The liquid crystal polymer composition of the present invention can be obtained by blending the above-mentioned wholly aromatic liquid crystal polymer, polyamide resin, and, if desired, the above-mentioned inorganic filler and / or organic filler, other additives, other resin components, etc. in a predetermined composition, and melt-kneading them using a Banbury mixer, a kneader, a single-screw or twin-screw extruder, etc. Alternatively, the liquid crystal polymer composition of the present invention can be obtained by dry-blending the wholly aromatic liquid crystal polymer and polyamide resin, and melt-kneading them in a molding machine.

[0079] From the viewpoint of film formability, etc., the liquid crystal polymer composition of the present invention has a tensile elongation at break of usually 1.2% or more, preferably 1.3 to 15%, and more preferably 1.4 to 10% in accordance with ISO 527-1 for a molded article made from the composition. A large value of the tensile elongation at break means that the elongation of the liquid crystal polymer composition is improved, and the film formability is improved.

[0080] From the viewpoint of film formability, etc., the liquid crystal polymer composition of the present invention has a bending strength of a molded article made from the composition of the present invention of usually 160 MPa or less, preferably 60 to 155 MPa, and more preferably 65 to 150 MPa, as determined by ISO 178. A smaller bending strength value means that the flexibility of the liquid crystal polymer composition is improved, and the film formability is improved.

[0081] From the viewpoint of film formability, etc., the liquid crystal polymer composition of the present invention has a flexural modulus of 10.0 GPa or less, preferably 1.5 to 9.7 GPa, and more preferably 2.0 to 9.5 GPa, in accordance with ISO 178, for a molded article made from the composition. A smaller flexural modulus value means improved flexibility of the liquid crystal polymer composition and improved film formability.

[0082] The liquid crystal polymer composition of the present invention has a melt volume flow rate (MVR) of 3 to 60 cm at 230°C under a load of 2160 g (low load) according to ISO 1133. 3 / 10 minutes, preferably 5 to 50 cm 3 / 10 minutes, preferably 7-40cm 3 / 10 minutes, more preferably 9 to 30 cm 3 / 10 minutes, and usually 170-500cm under a load of 20,000g (high load) 3 / 10 minutes, preferably 180-450cm 3 / 10 minutes, preferably 190-400cm 3 / 10 minutes, more preferably 200 to 350 cm 3 / 10 minutes.

[0083] Since the liquid crystal polymer composition of the present invention has a low crystalline melting temperature (210 to 250° C.), it easily melts and flows during molding, and the above-mentioned melt volume flow rate can be obtained even at a relatively low temperature.

[0084] The liquid crystal polymer composition of the present invention has a flow rate ratio, which is the value obtained by dividing the MVR at high load by the MVR at low load, of usually 11.5 to 40.0, preferably 12.0 to 35.0, more preferably 12.5 to 30.0, and even more preferably 13.0 to 25.0, in terms of film formability.

[0085] The liquid crystal polymer composition of the present invention is processed into molded products such as films, sheets, blow molded products, bottles, containers, packaging materials, machine parts, electric / electronic parts, building / civil engineering materials, home / office supplies, furniture parts, and daily necessities by known molding methods such as injection molding, extrusion molding, blow molding, etc. The temperature conditions during molding are preferably within the range of the crystalline melting temperature (210 to 250°C) of the wholly aromatic liquid crystal polymer used to the crystalline melting temperature + 40°C.

[0086] Examples of mechanical parts include gears, screws, springs, bearings, levers, cams, ratchets, and rollers.

[0087] Examples of electrical and electronic components include housings for copy machines, personal computers, printers, electronic musical instruments, home game consoles, and portable game consoles, as well as internal parts (connectors, switches, IC and LED housings, sockets, relays, resistors, condensers, coil bobbins, etc.).

[0088] Examples of architectural and civil engineering components include curtain parts, blind parts, roof panels, insulated walls, adjusters, plastic beams, and ceiling hanging equipment.

[0089] Examples of everyday items include various cutlery, various toiletry parts, prepaid cards, saw blades for household wrap, food tray cases, and food cups.

[0090] Examples of containers include containers for storing various contents such as food and beverages such as rice products, processed foods, side dishes, pickles, Japanese sweets, Western sweets, juices, alcoholic beverages, and seasonings, cosmetics such as hair styling products, foundations, and perfumes, and various detergents such as hand washing detergents, face washing detergents, kitchen detergents, laundry detergents, shampoos, and conditioners. Among these, the containers are particularly useful as containers for storing food and beverages.

[0091] Since the liquid crystal polymer composition of the present invention exhibits good film-forming properties, it is suitably processed into films, sheets, blow molded products, etc., and is suitably molded by extrusion molding or blow molding from the viewpoints of ease of molding, mass productivity, cost, etc.

[0092] When extrusion molding or blow molding is employed, the resin can be processed into a film, sheet, container, pipe, fiber, etc., and may be a single or single-layer molded article. From the viewpoint of improving function and reducing costs, the resin may be a composite molded article having a portion made of another resin composition, or a multi-layer molded article having a layer made of another resin composition. Films, sheets, fibers, etc. can also be uniaxially or biaxially stretched. The obtained molded article may be subjected to secondary processing such as bending, vacuum forming, blow molding, and press molding to obtain a desired molded article, if necessary.

[0093] In the case of forming a multi-layered molded article, it is preferable to use the layer of the liquid crystal polymer composition of the present invention as a gas barrier layer in an intermediate layer from the viewpoint of the gas barrier property of the molded article. In addition, when laminating the layer of the liquid crystal polymer composition of the present invention and the layer of another resin composition, from the viewpoint of improving adhesion, an adhesive layer or the like may be formed between the layer of the liquid crystal polymer composition and the layer of another resin composition.

[0094] Furthermore, the molded article made of the liquid crystal polymer composition of the present invention can be processed into a desired molded article by blow molding, which is suitable for molding hollow products such as bottles. Specific blow molding methods include direct blow molding, injection blow molding, and free blow molding. In addition, the molded article made of the liquid crystal polymer composition of the present invention can be processed into a desired molded article by extrusion molding, which is suitable for molding membrane products such as films and sheets. Specific extrusion molding methods include inflation molding and T-die molding.

[0095] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. EXAMPLES

[0096] The crystalline melting temperature, tensile elongation at break, bending strength, bending modulus and flow rate ratio in the examples were measured by the methods described below.

[0097] <Crystal Melting Temperature> The measurement was carried out using a differential scanning calorimeter (DSC) Exstar6000 manufactured by Seiko Instruments Inc. A liquid crystal polymer sample was measured under conditions of a temperature rise of 20°C / min from room temperature, and after observing the endothermic peak temperature (Tm1), it was held at a temperature 20 to 50°C higher than Tm1 for 10 minutes. Next, the sample was cooled to room temperature under conditions of a temperature drop of 20°C / min, and then measured again under conditions of a temperature rise of 20°C / min, and the endothermic peak was observed. The temperature showing the peak top was taken as the crystalline melting temperature of the wholly aromatic liquid crystal polymer.

[0098] <Tensile elongation at break> Using an injection molding machine (UH1000-110 manufactured by Nissei Plastic Industrial Co., Ltd.), injection molding was performed at a cylinder setting temperature of 250°C and a mold temperature of 80°C to prepare a type A1 dumbbell test piece having a thickness of 4.0 mm. Using an autograph AG-Xplus (a universal testing machine manufactured by Shimadzu Corporation), measurements were performed in accordance with ISO 527-1 at a test speed of 50 mm / min and a chuck distance of 115 mm. A large value of tensile elongation at break means that the elongation of the liquid crystal polymer composition is improved, and film formability is improved.

[0099] <Flexural strength, flexural modulus> Using an injection molding machine (UH1000-110 manufactured by Nissei Plastic Industrial Co., Ltd.), a rectangular test piece having a length of 80.0 mm, a width of 10.0 mm, and a thickness of 4.0 mm was prepared at a cylinder setting temperature of 250°C and a mold temperature of 80°C. Measurements were performed in accordance with ISO 178 using an INSTRON5567 (a universal testing machine manufactured by Instron Japan Co., Ltd.) under conditions of a span distance of 64 mm and a compression speed of 2 mm / min. Small values ​​of bending strength and bending modulus indicate improved flexibility of the liquid crystal polymer composition and improved film formability.

[0100] <Flow rate ratio> The MVR of the liquid crystal polymer composition at low load and high load were measured at 230°C under conditions of a load of 2160g (low load) and a load of 20000g (high load) in accordance with ISO 1133 using a Melt Indexer G-02 manufactured by Toyo Seiki Seisakusho Co., Ltd., and the flow rate ratio was calculated. A large value of the flow rate ratio means excellent film formability.

[0101] <Film-forming property evaluation> The film-forming properties were evaluated based on the occurrence rate of cracks and the stretchability described below. (Crack occurrence rate) Using an extruder (Labo Plastomill 3S150 manufactured by Toyo Seiki Seisakusho Co., Ltd.), a film 20 cm wide, 30 cm long, and 100 μm thick was produced by the T-die method at a cylinder temperature of 240°C. 20 points of the obtained film were folded 180° parallel to the MD direction. The 20 folds were visually observed for the presence or absence of cracks or tears, and the occurrence rate of cracks was evaluated according to the following criteria and used as an index of film formability. The smaller the occurrence rate of cracks (the higher the value of the evaluation criteria below), the better the film formability. [Evaluation Criteria] 5: The crack occurrence rate is less than 10% 4: The crack occurrence rate is between 10% and 20%. 3: The crack occurrence rate is between 20% and 30%. 2: The crack occurrence rate is between 30% and 40%. 1: Crack occurrence rate is 40% or more

[0102] (Stretchability) When a film was produced by the T-die method using an extruder (Labo Plastomill 3S150 manufactured by Toyo Seiki Seisakusho Co., Ltd.) at a cylinder temperature of 240°C, the molten resin composition coming out of a die with a die width of 20 cm was pulled in the TD direction to produce 20 films with a width (length in the TD direction) of about 40 cm, a length of 30 cm, and a thickness of 50 μm. The 20 films produced were visually observed for the presence or absence of breakage, and the rate of breakage was evaluated according to the following criteria. The smaller the rate of breakage (the higher the value of the evaluation criteria below), the easier it was to stretch during film production and the better the film-forming properties. [Evaluation Criteria] 5: The rate of breakage is less than 10% 4: The rate of breakage is between 10% and 20%. 3: The rate of breakage is between 20% and 30%. 2: The rate of breakage is between 30% and 40%. 1: The rate of breakage is 40% or more.

[0103] In the examples and comparative examples, the following abbreviations represent the following compounds. LCP: Fully aromatic liquid crystal polymer PA: Polyamide resin POB: 4-hydroxybenzoic acid BON6: 6-hydroxy-2-naphthoic acid BP: 4,4'-dihydroxybiphenyl HQ: Hydroquinone TPA: Terephthalic acid

[0104] (Synthesis of Liquid Crystal Polymer) [Synthesis example 1 (LCP-1)] A reaction vessel equipped with a stirrer with a torque meter and a distillation tube was charged with 349.3 g (40 mol%) of POB, 476.0 g (40 mol%) of BON6, 69.7 g (10 mol%) of HQ, and 105.0 g (10 mol%) of TPA, and further charged with 1.03 times the moles of acetic anhydride relative to the amount (mol) of hydroxyl groups in the total monomers, and deacetic acid polymerization was carried out under the following conditions.

[0105] The temperature was raised from room temperature to 145°C in 1 hour under a nitrogen gas atmosphere, and the temperature was maintained for 30 minutes. Next, the temperature was raised to 330°C over 7 hours while distilling off the by-product acetic acid, and then the pressure was reduced to 10 mmHg over 80 minutes. The polymerization reaction was terminated when a predetermined torque was reached, the contents were removed from the reaction vessel, and pellets of a wholly aromatic liquid crystal polyester resin were obtained using a pulverizer. The amount of acetic acid distilled during polymerization was almost the theoretical value. The crystal melting temperature (Tm) of the obtained LCP pellets measured by DSC was 218°C.

[0106] [Synthesis example 2 (LCP-2)] A reaction vessel equipped with a stirrer with a torque meter and a distillation tube was charged with 323.2 g (36 mol%) of POB, 48.9 g (4 mol%) of BON6, 323.9 g (30 mol%) of TPA, 169.4 g (14 mol%) of BP, and 114.5 g (16 mol%) of HQ, and further charged with 1.03 times the moles of acetic anhydride relative to the amount (mol) of hydroxyl groups in the total monomers, and deacetic acid polymerization was carried out under the following conditions.

[0107] The temperature was raised from room temperature to 145°C over 1 hour under a nitrogen gas atmosphere, and then maintained at 145°C for 30 minutes. Next, the temperature was raised to 350°C over 7 hours while distilling off the by-product acetic acid, and the pressure was reduced to 5 mmHg over 80 minutes. The polymerization reaction was terminated when a predetermined torque was reached, and the contents were removed from the reaction vessel and pellets of LCP were obtained using a pulverizer. The amount of acetic acid distilled during polymerization was almost the theoretical value. The Tm of the obtained pellets measured by DSC was 335°C.

[0108] (Polyamide resin) The following polyamide resins were used: Polyamide resin: "Polyamide 6 (EX-6240)" (specific gravity: 1.01) manufactured by Unitika Ltd.

[0109] [Examples 1-2 and Comparative Examples 1-2] LCP-1 to 2 and polyamide resin were mixed in the amounts shown in Table 1, and melt-kneaded using a twin-screw extruder (TEX-30, manufactured by Nippon Steel Corporation) at a cylinder temperature of LCP crystal melting temperature +10 to +40°C to obtain pellets of a liquid crystal polymer composition. The obtained pellets were used to measure the tensile elongation at break, bending strength, bending modulus, and flow rate ratio by the above-mentioned methods. In addition, a film having a thickness of 100 μm was produced by the T-die method, and the film formability was evaluated based on the above-mentioned evaluation criteria. The results are shown in Table 1.

[0110] As shown in Table 1, the liquid crystal polymer compositions of Examples 1 and 2 all had a tensile elongation at break of 2.1 to 3.2%, a bending strength of 134 to 144 MPa, a bending modulus of elasticity of 7.5 to 8.1 GPa, and a flow rate ratio of 14.3 to 14.7, and were more flexible and had improved film formability than those of Comparative Example 1 that did not contain a polyamide resin. 2 All of the liquid crystal polymer compositions were superior to Comparative Example 1 in film formability based on the above evaluation criteria.

[0111] On the other hand, in the liquid crystal polymer composition of Comparative Example 2, the crystalline melting temperature of LCP-2 was high, and the polyamide resin was thermally deteriorated during melt kneading, generating decomposition gas, and the extrusion of the extrusion strand was unstable, so that a liquid crystal polymer composition could not be obtained.

[0112] [Table 1]

Claims

1. A liquid crystal polymer composition comprising 100 parts by mass of a wholly aromatic liquid crystal polymer having a crystalline melting temperature of 210 to 250° C. and 1 to 65 parts by mass of a polyamide resin, and having a tensile elongation at break of 1.2 to 15% according to ISO 527-1.

2. 2. The liquid crystal polymer composition according to claim 1, wherein the wholly aromatic liquid crystal polymer has a crystalline melting temperature of 215 to 245°C.

3. The wholly aromatic liquid crystal polymer is represented by the formulas (I) to (IV): 【Chemistry 1】 [In the formula, Ar 1 and Ar 2 each represents one or more kinds of divalent aromatic groups, and p, q, r and s each represent a composition ratio (mol %) of each repeating unit in the wholly aromatic liquid crystal polyester, and satisfy the following condition: 0.5≦p / q≦2.5 2≦r≦15, and 2≦s≦15] 3. The liquid crystal polymer composition according to claim 1, which is a wholly aromatic liquid crystal polyester comprising a repeating unit represented by the following formula:

4. Formula (III) and / or Formula (IV) are Ar 1 and Ar 2 are independently represented by the formulas (1) to (4). 【Chemistry 2】 4. The liquid crystalline polymer composition of claim 3, comprising one or more repeat units which are aromatic groups selected from the group consisting of:

5. 5. The liquid crystal polymer composition according to claim 1, wherein the polyamide resin is polyamide 6.

6. A molded article made of the liquid crystal polymer composition according to any one of claims 1 to 5.

7. The molded article according to claim 6, wherein the molded article is a film, a sheet or a blown article.

Citation Information

Patent Citations

  • Film of liquid crystal polyester resin composition and its production

    JP1996337710A

  • Thermoplastic resin composition

    JP1997031310A

  • Molecular composite material comprising liquid crystal polymer and polyamide and its production

    JP1997067504A

  • Polymer alloy and its film

    JP2000290512A

  • Liquid crystal polymer blend film

    JP2004175995A